2018
DOI: 10.1093/mnras/sty1556
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for molecular hydrogen chemistry coupled to radiation hydrodynamics

Abstract: We introduce non-equilibrium molecular hydrogen chemistry into the radiation hydrodynamics code Ramses-RT. This is an adaptive mesh refinement grid code with radiation hydrodynamics that couples the thermal chemistry of hydrogen and helium to moment-based radiative transfer with the Eddington tensor closure model. The H 2 physics that we include are formation on dust grains, gas phase formation, formation by three-body collisions, collisional destruction, photodissociation, photoionization, cosmic ray ionizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 107 publications
(173 reference statements)
3
29
0
Order By: Relevance
“…The self-shielding prescription is able to block most of the LW photons from entering into the molecular layer prducing a relatively sharp and thin H I layer between the fully ionized H II and fully molecular H 2 layers. This nicely matches with the results obtained by Nickerson et al (2018), thereby confirming the accuracy of our scheme. This paper has been typeset from a T E X/L A T E X file prepared by the author.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The self-shielding prescription is able to block most of the LW photons from entering into the molecular layer prducing a relatively sharp and thin H I layer between the fully ionized H II and fully molecular H 2 layers. This nicely matches with the results obtained by Nickerson et al (2018), thereby confirming the accuracy of our scheme. This paper has been typeset from a T E X/L A T E X file prepared by the author.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, our formulation of the RT equations does not track the optical depth of individual rays. Therefore, we resort to using the method described in Nickerson et al (2018) and boost the destruction of LW photons by a constant factor to incorporate the fact that only a fraction of LW photon absorption leads to H2 dissociation. As the LW photons propagate through gas cells, their repeated destruction mimics the column density variation of H2 destruction rates.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the entire body of work between Nickerson et al (2018) and this present paper, we have shown that the laws that govern H 2 on the chemical scale give rise to relations that govern H 2 on the galactic scale. We have demonstrated that high resolution is critical in galaxy simulations to properly form H 2 without the need for a clumping factor.…”
Section: Discussion and Summarymentioning
confidence: 63%
“…What we do instead is to enhance LW destruction at each time-step but not H 2 dissociation, and thereby do not require a conversion to column density because the LW photons will travel through the column of cells with each timestep. We calibrate the factor of LW destruction enhance-ment with one-dimensional simulations of radiation dissociating an H 2 slab (see Nickerson et al 2018). We compare our transition between H 2 and Hi with its position as predicted by the analytical model of Bialy et al (2017), and find that enhancing the LW destruction by a factor of 400 gives good results for a range of incident fluxes, slab densities, and metallicities (Nickerson et al 2018).…”
Section: Gas Chemistrymentioning
confidence: 94%
See 1 more Smart Citation